Analysis of Factors Influencing Consumers' Purchase Intention Based on Perceived Value in E-commerce Clothing Pre-sale Model (Journal of Fiber Bioengineering and Informatics, 2023)
The e-commerce pre-sale model for apparel is a kind of marketing method for retailers to generate actualconsumption through online consumers' payment of deposits or full payments. The online apparel'sre-sale model, an effective competition, can effectively reduce inventory, predict production and increasethe actual profits of enterprises. Based on the perceived value of consumers, SPSS21.0 and AMOS21.0are used to analyze the collected information, verify the hypotheses of the initial model of consumers' purchase intention under the pre-sale model, and then make modifications. The relationship amongvariables can be revealed and this paper explains the performance of the influence of pre-sale mode onconsumers' purchase intention, by analyzing correlations among perceived benefit, perceived sacrificeand perceived value, as well as the impact on purchase intention.
Keywords: Pre-sale; E-commerce; Perceived Value; Purchase Intention